2010
DOI: 10.1007/s10531-010-9951-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing conservation priorities of xenarthrans in Argentina

Abstract: In this study, we combine species distribution models with a reserve selection approach to assess the degree of representation of xenarthrans in the existing protected area network of Argentina, and to identify conservation priority areas that may help expand the current system. Species distribution models were developed from species' occurrence records using a maximum entropy algorithm. Maps of species distributions were produced for 15 of the 16 species currently present in the country. To assess the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
12
0
6
Order By: Relevance
“…Otros problemas son la escasa representación en unidades de conservación, la caza directa, ataques por parte de perros y atropellamientos en carreteras (Fallabrino & Castiñeira, 2006;Fallabrino et al, 2009). Esta problemática común a todos los xenartros ya ha sido detectada en trabajos recientes de distribución y conservación realizados en Argentina (Tognelli et al, 2010;Abba et al, 2012). A su vez, cambios relevantes en el uso de suelo proyectados a corto plazo para Uruguay (Achkar et al, 3 Detalle de la distribución potencial de Cabassous tatouay para Uruguay, superpuesta con las áreas del SNAP ingresadas (perí-metros en color rojo) o en proceso de ingreso (perímetros de color violeta o círculos de colores).…”
Section: Datos De Presencia Y Rango De Distribuciónunclassified
“…Otros problemas son la escasa representación en unidades de conservación, la caza directa, ataques por parte de perros y atropellamientos en carreteras (Fallabrino & Castiñeira, 2006;Fallabrino et al, 2009). Esta problemática común a todos los xenartros ya ha sido detectada en trabajos recientes de distribución y conservación realizados en Argentina (Tognelli et al, 2010;Abba et al, 2012). A su vez, cambios relevantes en el uso de suelo proyectados a corto plazo para Uruguay (Achkar et al, 3 Detalle de la distribución potencial de Cabassous tatouay para Uruguay, superpuesta con las áreas del SNAP ingresadas (perí-metros en color rojo) o en proceso de ingreso (perímetros de color violeta o círculos de colores).…”
Section: Datos De Presencia Y Rango De Distribuciónunclassified
“…Other studies carried out in Argentina have also clearly shown that protected areas are ineffective or insufficient for the preservation of biological diversity (Arzamendia & Giraudo, 2004;Nori et al, 2013;Tognelli et al, 2011). Although the protected areas are partial solutions to habitat degradation, they are also cornerstones of conservation (Margules & Pressey, 2000).…”
Section: Protected Areasmentioning
confidence: 99%
“…Worse still it is not clear which target is required to safeguard an individual species (Pidgeon, Rivera, Martinuzzi, Politi, & Bateman, 2015). Regarding vertebrates, Rodrigues et al (2004) considered that conserving 10% of the land surface was enough if the species is widely distributed, and that this percentage must be higher, 70%-100%, if the species has a restricted distribution (Kukkala & Moilanen, 2012;Tognelli et al, 2011). However, Howard et al (1998) and Kerr (1997) sustained that the minimum requirements to conserve the diversity of vertebrates will not necessarily be an effective umbrella for biodiversity in general, because many other more diverse groups (including plants and invertebrates) are expected to require considerably larger areas to be fully represented.…”
Section: Biodiversity Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…La modificación de hábitats naturales relacionadas a la agricultura puede ejercer presiones positivas en las poblaciones de armadillos (Merrit, 2008; Abba y Vizcaíno, 2011) aunque en la mayoría de los casos la agricultura y el pastoreo se consideran presiones negativas (Aguiar y Fonseca, 2008;Tognelli et al, 2011). El estado de conservación de los…”
Section: Introductionunclassified